IN VITRO VALIDATION OF SEX SORTED BULL SEMEN PRODUCED USING FLOW CYTOMETRIC METHOD - S. Rangasamy; S. Balasubramanian; G. Dhinakar Raj; A. Palanisammi; D. Reena; R. Chitra (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A commercially procured flow cytometrically sorted semen was reanalyzed to validate the effect of flow cytometry on structural and functional viability of spermatozoa. Flow cytometric analysis of commercially procured sex sorted frozen thawed bull semen showed the percentage of X sperms to be 95.31± 0.21 and Y sperms to be 4.69 ± 0.27, respectively. As expected sexed sperm had lower post thaw motility than the non-sexed sperm. However, no significant differences in the percentage of sperms with intact acrosome and expression of ROS were observed. Interestingly, DNA fragmentation index was statistically lower for the commercially procured sorted than for unsorted frozen thawed bull semen.